Development of New CAPS/dCAPS and SNAP Markers for Rice Eating Quality - LESTARI, PUJI; KOH, HEE JONG (HAYATI Journal of Biosciences, 2013)
Rice eating quality traits are very complex and essential to be evaluated not only through physicochemical analysis and sensory test but also by PCR-based marker approach. To date, simple markers based on single nucleotide polymorphism (SNP) discovery to evaluate eating quality of cooked rice are still limited. Thus, the aims of this study were to develop PCR-based markers, called SNAP (single nucleotide amplified polymorphism) as alternative markers of cleaved amplified polymorphic sequence/derived cleaved amplified polymorphic sequence (CAPS/dCAPS). Four primer pairs specific to targeted alleles (CAPS/dCAPS and SNAP) of four loci were successfully designed based on the discovered SNPs according to the eating quality-QTL and searching genomic database. The primer pairs were able to identify alleles corresponding loci among indica and japonica varieties with diverse palatability (overall eating quality). There was consistent allele pattern produced by SNAP and CAPS/dCAPS for the same base mutation. The SNAP marker for rice eating quality trait could be easily assayed by standard agarose gel electrophoresis, allowing to increase the advantage of genotyping methods. Moreover, the SNAP markers together with our previous developed markers which were recommended as applicable marker set for evaluation of rice eating quality, will facilitate as marker-assisted selection for rice breeding program.